Game-based learning for teaching English to Thai pharmacy students - Methaneethorn, Janthima; Sudchada, Patcharaporn; Insuk, Suppachai (Kasetsart Journal of Social Sciences, 2021)
The aims of this study were to test and to evaluate a game-based learning (GBL) approach for teaching English to Thai pharmacy students. GBL model was applied in a fifteen-week semester English course for second-year university pharmacy students. The course met once a week for two hours. During each class, the students were divided into small groups of 4–5 to participate in three educational games related to vocabulary, pronunciation, and sentence creation. At the completion of each game, the teacher held a discussion with the students. The effectiveness of the game-based model was evaluated by a pre-test at the start of the semester and a post-test at the end of the semester. Both tests covered knowledge of vocabulary, knowledge of grammar, and self-assessment of vocabulary and grammar competency. Pronunciation skills were evaluated in the semester midterm and final exams. The students showed significant improvement in vocabulary knowledge (mean difference = 1.39, p < .001) as well as improvement of self-confidence in grammar and vocabulary proficiency (mean difference = 3.02 and 3.00, respectively, p < .001). The findings suggest that GBL model used in this course has shown a positive impact on the English abilities of Thai pharmacy students. This model can be applied to other English classes taught to Thai pharmacy students.